Analisis Beban Pelayanan Kesehatan Dan Kesiapsiagaan Daerah Akibat Banjir Di Provinsi Sumatera Utara Tahun 2025: Studi Data Sekunder PUSDALOPS PB BPBD Sumut - Surya Utama; Balqis Nurmauli Damanik (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
This study analyzes the burden on health services and the level of regional preparedness during the 2025 flood disaster in North Sumatra Province. Using a descriptive-analytic design with secondary data obtained from official disaster reports, this research examines the number of affected households, displaced populations, mortality, and emergency response status across 18 districts and cities. Findings show significant variations in the magnitude of impacts, with regions experiencing higher numbers of affected populations demonstrating greater pressure on health services, particularly in emergency care, communicable disease prevention, and shelter-based health management. Furthermore, regions that activated emergency response status earlier and demonstrated stronger preparedness were found to experience lower health burdens. These results highlight the importance of integrating disaster preparedness into local health system planning to strengthen resilience against hydrometeorological disasters. The study emphasizes the need for improved intersectoral coordination, enhanced health logistics capacity, and readiness of health personnel to respond effectively to large-scale emergencies.